Whose devolution is it anyway? divergent constructs, interests and capacities between the poorest forest users and states - Edmunds, D.; Wollenberg, Eva Karoline (Routledge, 2003)
This chapter synthesizes results from case studies of the effects of devolution policies on the management of forests in three Asian countries, China, India and the Philippines. It also seeks to explain the disappointing impacts of forest devolution policies in terms of the divergent interests and perceptions of forest departments and local people. Some case studies show the convergence of between state and local interest. Some give examples where local interests have prevailed in spite of state strategies to maintain control. The principle for forest policy should be to create sustainable livelihoods for local resource users, especially the poorest among them, rather than reducing the cost of government forest administration.